Anesthetic spindles serve as EEG markers of the depth variations in anesthesia induced by multifarious general anesthetics in mouse experiments - You, Ying; Liu, Hui; Yang, Zhanfei; Chen, Yuxuan; Yang, Fei; Yu, Tian; Zhang, Yu (Frontiers in Pharmacology, 2024)
Background: Mice play a crucial role in studying the mechanisms of general anesthesia.However, identifying reliable EEG markers for different depths of anesthesia induced by multifarious agents remains a significant challenge. Spindle activity, typically observed during NREM sleep, reflects synchronized thalamocortical activity and is characterized by a frequency range of 7 to 15 Hz and a duration of 0.5 to 3 seconds.Similar patterns, referred to as "anesthetic spindles," are also observed in the EEG during general anesthesia. However, the variability of anesthetic spindles across different anesthetic agents and depths is not yet fully understood.Method: Mice were anesthetized with dexmedetomidine, propofol, ketamine, etomidate, isoflurane, or sevoflurane, and cortical EEG recordings were obtained. EEG signals were bandpass filtered between 0.1 and 60 Hz and analyzed using a custom MATLAB script for spindle detection. Anesthesia depth was assessed based on Guedel's modified stages of anesthesia and the presence of burst suppression in the EEG.Results: Compared to sleep spindles, anesthetic spindles induced by the different agents exhibited higher amplitudes and longer durations. Isoflurane-and sevoflurane-induced spindles varied with the depth of anesthesia. Spindles associated with etomidate were prominent during induction and light anesthesia, whereas those induced by sevoflurane and isoflurane were more dominant during deep anesthesia and emergence. Postanesthesia, spindles persisted but ceased more quickly following inhalational anesthesia.Conclusion: Anesthesia spindle waves reflect distinct changes in anesthesia depth and persist following emergence, serving as objective EEG markers for assessing both 4 4 anesthesia depth and the recovery process.